A Place-Based Approach to Inclusive Growth: A Development Path Towards Greater Sustainability in Tunisia - Abbassi, Nessrine; Benhamed, Adel (Journal of Posthumanism, 2025)
The aim of this work is to identify the conditions for inclusive growth, to make a significant contribution to a more sustainable transition in a developing country. The emergence of new challenges from a global perspective requires regional explanations more than ever. Currently, our planet is being faced with economic and social challenges caused by the financial crisis and taken up by the Sustainable Development Goals in 2015. Using a diversified theoretical corpus of inclusive growth, this study also aims to explore data in relation to inclusion and exclusion in a spatially explicit context. Beside this, the main hypothesis of this work is to give particular attention to the place-based approach in contextualizing and reflecting on the inclusive growth objectives within a country such as Tunisia. Thus, we use a corpus of information that integrates data post 2011 reflecting the inequalities of access and inclusion towards an inclusive and sustainable transition in Tunisia. By consolidating the link between the inclusive growth objectives and sustainable development, we conclude that a territorial approach is a necessary condition for analyzing more closely the processes for more sustainable regional inclusion.